2018
DOI: 10.1111/jdv.15024
|View full text |Cite
|
Sign up to set email alerts
|

Alitretinoin can be a good treatment option for idiopathic recalcitrant trachyonychia in adults: an open‐label study

Abstract: For the first time, this study evaluated the efficacy and safety of oral alitretinoin for idiopathic recalcitrant trachyonychia in adults. The results suggest that oral alitretinoin can be a good treatment option for adult patients with recalcitrant trachyonychia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The second publication was a case series that discussed the usage of alitretinoin (first-generation retinoid) 30 mg daily for at least three months in the management of idiopathic recurrent trachyonychia in 21 patients. This study reported some improvement in 98.1% of 210 nails and complete improvement in 22.9% of 210 nails after three months of alitretinoin treatment [14]. Lastly, acitretin 0.4 mg/kg (25 mg) in combination with topical clobetasol 8% was successfully used to manage idiopathic trachyonychia with nail resolution after roughly one year [15].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The second publication was a case series that discussed the usage of alitretinoin (first-generation retinoid) 30 mg daily for at least three months in the management of idiopathic recurrent trachyonychia in 21 patients. This study reported some improvement in 98.1% of 210 nails and complete improvement in 22.9% of 210 nails after three months of alitretinoin treatment [14]. Lastly, acitretin 0.4 mg/kg (25 mg) in combination with topical clobetasol 8% was successfully used to manage idiopathic trachyonychia with nail resolution after roughly one year [15].…”
Section: Discussionmentioning
confidence: 72%
“…Paradoxical to our case, retinoids have been described as possible treatment options for patients with idiopathic recurrent trachyonychia and occupational trachyonychia in several studies [13][14][15]. The first was a case report of a patient with a past history of psoriasis who worked as a jeweler and subsequently developed occupational trachyonychia secondary to a microtrauma; this was successfully treated with 0.3 mg/kg of acitretin daily [13].…”
Section: Discussionmentioning
confidence: 74%
“…In addition, oral alitretinoin was found beneficial in treating isolated recalcitrant trachyonychia, achieving complete treatment response in 50% (6 of 12 patients) within 6 months of treatment. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recently, alitretinoin was reported beneficial in idiopathic recalcitrant trachyonychia. [ 11 ] Currently, treatment efficacy data are derived from non-comparative small case series and case reports.…”
Section: Introductionmentioning
confidence: 99%
“…Topical agents include topical steroids, calcineurin inhibitors, and calcipotriol/betamethasone dipropionate ointments 13 . If there is no improvement after 3 months of topical treatment, intralesional steroid injection 14 or systemic medications such as systemic steroids, cyclosporine, and alitretinoin can be considered 12,15,16 . However, as there is insufficient data regarding the management, further studies are warranted to establish an ideal management strategy.…”
Section: Discussionmentioning
confidence: 99%